1996
DOI: 10.1111/j.1540-8159.1996.tb03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of QT Intervals: An Alternative Approach to QT Dispersion

Abstract: QT dispersion (QTd) describes the heterogeneity of ventricular repolarization on the basis of the temporal range of QT intervals as measured in the 12-lead ECG. We examined the spatial distribution of QTd using multichannel magnetocardiograms (MCGs), which noninvasively register changes in magnetic field strength at 37 sites over the heart. As in ECG, the MCG signal in each channel may be used to measure QT interval. By calculating QT deviation from QTmin at each site, one can reconstruct the spatial distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
1
17
0
2
Order By: Relevance
“…The evaluation of spatial QT dispersion on MCG, reflecting regional heterogeneity of repolarization, may improve the identification of CAD patients. 18, 38 In this study, we demonstrated not only that the patients with significant CAD had significantly higher prevalence of early occurrence of +T-wave propagation and increased heterogeneity (QTc dispersion and SI-QTc), but also that the repolarization heterogeneity index has superior diagnostic accuracy to T-wave propagation mapping in the patients with suspected CAD (0.79 vs. 0.65; P=0.036).…”
Section: Resultsmentioning
confidence: 72%
“…The evaluation of spatial QT dispersion on MCG, reflecting regional heterogeneity of repolarization, may improve the identification of CAD patients. 18, 38 In this study, we demonstrated not only that the patients with significant CAD had significantly higher prevalence of early occurrence of +T-wave propagation and increased heterogeneity (QTc dispersion and SI-QTc), but also that the repolarization heterogeneity index has superior diagnostic accuracy to T-wave propagation mapping in the patients with suspected CAD (0.79 vs. 0.65; P=0.036).…”
Section: Resultsmentioning
confidence: 72%
“…ANG II-induced electrical remodeling is part of the pathophysiological process in hypertensive heart disease and accounts for an increased arrhythmia burden in these patients. Several clinical CMFM studies suggested that multichannel CMFM systems can detect an increased risk in life-threatening arrhythmias (18,19,34). We believe the perspectives of the CMFM technique lie in determining nonhomogeneous aspects of depolarization and repolarization before the conventional ECG can detect these changes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, multichannel MCG systems provide simultaneous multipoint cardiac mapping, with spatial and temporal resolution adequate to reveal electrophysiological markers for risk of life-threatening arrhythmias (43,44,74). In experimental animal studies, only a few of the 12 ECG leads are usually recorded (9,18,24,47), although high-quality multichannel BSPM in rats has been reported (3,8,49,66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Multichannel MCG mapping measures the magnetic fields (MF) generated by cardiac activation currents, with minimal distortion due to the shape and conductivity of the lungs and torso (20, 28). The advantages of contactless MCG mapping are as follows: 1) the ability to study conscious animals without movement artifacts (65), 2) the potential to provide diagnostic information not revealed by ECG (1,29,36,37,41,43,44,51,54,62,64,69,71,74,75), 3) the fixed-sensors geometry (42), which minimizes errors in localization of intracardiac sources (30) and three-dimensional electroanatomic imaging of arrhythmogenic phenomena (77), and 4) the localization of VR heterogeneities associated with areas of myocardial injury (50).A major problem with MCG mapping of small hearts might be an unfavorable signal-to-noise ratio (S/N), because the cardiac sources are very weak. For this reason, most experimental MCG studies of small animal hearts have been performed in magnetically shielded rooms (4,22,23,65,72).…”
mentioning
confidence: 99%